Obszary integracji zrównoważonej karty wyników i rachunku odpowiedzialności w przedsiębiorstwach zorientowanych procesowo - Szydełko, Łukasz (The integration fields of balanced scorecard and responsibility accounting in the process-oriented enterprises, 2006)
Balanced Scorecard consists of four perspectives, such as finance, client, internal processes and innovation and growth. This instrument enables to translate the strategy into action. The strategic goals which are involved in strategy should be cascaded at lower levels in company. It determines cascading the balanced scorecard. We should choose internal parts (segments) in enterprises in which we provide scorecard. They are process responsibility centers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 391-399